(untitled) (Mantichora. Italian Journal of Performance Studies, 2026)
This article investigates the shifting status of plants in Western culture and performing arts, moving from passive objects and symbolic devices to active, performative agents. After tracing the philosophical and cultural marginalization of plants—from Aristotle’s hierarchy of souls to their metaphorical use in canonical works such as Machiavelli’s La Mandragola and Shakespeare’s Macbeth—the study engages recent scientific and philosophical debates on plant intelligence and more-than-human agency. Framed within Environmental Humanities and new materialist thought, it explores how contemporary performance practices challenge anthropocentrism by recognizing vegetal agency through ecodramaturgy, bioperformativity, and ecoscenography. Focusing on Italian theatre-nature experiences, including the works of Lorenza Zambon, Nina’s Drag Queen, and Elena Borgna, the article demonstrates how plants become co-authors in site-specific and ecological performances. Rather than serving as backdrop or metaphor, flora participates in a relational, eco-centric creative process that redefines theatricality as interspecies co-creation and repositions humans within broader ecological systems.